Association of Peripheral Monocyte Count with Soluble P-Selectin and Advanced Stages in Nasopharyngeal Carcinoma - Adi Surya Komala; Andhika Rachman (Advances in Hematology)
Introduction. Inflammation is widely recognized to play an important role in cancer progression and is related to thrombosis. Soluble P-selectin (sP-selectin) is one of several biomarkers that may be predictive of thrombosis in cancer. This study aimed to investigate the correlation between monocyte count and sP-selectin in various stages of nasopharyngeal carcinoma. Methods. Fifty-five patients with nasopharyngeal carcinoma were divided into three groups according to nodal and distant metastasis (group of stages I-IVA, IVB, and IVC). Monocyte count was calculated from routine peripheral blood examination, while sP-selectin level was measured using commercial ELISA kit. Results. The monocyte count of subjects in groups IVB and IVC was significantly higher compared to group I-IVA (707/μL versus 528/μL, p=0.022; 841/μL versus 528/μL, p=0.005). Plasma levels of sP-selectin in group IVC were higher than group I-IVA (59.5 ng/mL versus 41.97 ng/mL, p=0.001) and group IVB (59.5 ng/mL versus 45.53 ng/mL, p=0.007). In subjects with high monocyte count (>665/μL), there was moderate correlation between monocyte count and sP-selectin (r=0.436, p=0.022). Conclusion. Advanced stages of nasopharyngeal carcinoma had higher levels of monocyte count and sP-selectin compared to earlier stages. Monocyte count was correlated with sP-selectin especially in high monocyte count subgroup.